(untitled) (American Journal of Education and Technology, 2022)
The study aimed to determine the learning styles and learning abilities of grade 6 pupils in dealing with modular learning. A descriptive design was used in this study. The survey was conducted in Lt. Andres Calungsud Elementary School to 30 elementary pupils who are enrolled in modular learning for School Year 2021-2022 and the majority of them were male pupils. A Researcher-made survey questionnaire was used in data gathering. Frequency and percentage distribution, mean and standard deviation, megastat were used in treating the data. The study revealed that the pupils have difficulty dealing with terms in their modules. Data show that the respondents got the highest mean in visual learning style interpreted as Often (M=2.60) and the lowest mean in auditory learning style. The respondent’s learning style in reading/writing got the lowest overall mean Sometimes (OM=1.94). The study found out that the highest problem encountered by the students in dealing with modular learning is confused by words. Data show that the respondent’s Digital - age Literacy type Learning Abilities got the highest mean of Sometimes (M=2.17) in the item “I feel comfortable using digital devices”. The respondent’s learning ability in problem-based thinking and problem-solving got the lowest mean of Sometimes. The Elementary pupils are highly satisfied with how teachers showed interest in helping students to develop personal skills and qualities. Moreover, the respondents are least satisfied with how they received sufficient advice and guidance in relation to the module. Finally, there is a significant difference in the learning styles and learning abilities of respondents.